Lingonberry Leaves Modify Rumen Protozoa Population, Carbohydrate Digestion, and Morphology of Gastrointestinal Tract in Sheep: A Preliminary Study - Małgorzata P. Majewska; Renata Miltko; Grzegorz Bełżecki; Marcin Barszcz; Misza Kinsner; Barbara Kowalik (Molecules)
Leaves, the main by-product of lingonberry harvesting, can be effectively used as a functional feed additive due to their health-promoting properties. This study evaluated the effects of lingonberry leaf (LL) supplementation on rumen fermentation, protozoal populations, and gastrointestinal morphology in sheep. Eight one-year-old Polish Mountain Sheep ewes (mean body weight: 33 kg) were allocated to a control (basal diet; forage-to-concentrate ratio 60:40) or an experimental group (basal diet + 9.30 g/kg DM dried LLs) in a completely randomised design (n = 4 per group) over 34 days. Both diets were formulated to be isoenergetic and isonitrogenous. LL additive significantly reduced Isotrichidae protozoal counts (p < 0.001) and ruminal pectinolytic activity (p = 0.043), without altering short-chain fatty acid (SCFA) or methane concentrations (p > 0.1). Histological analyses showed increased ruminal papilla width and surface area (p < 0.001) and decreased duodenal villus height and muscular layer thickness (p < 0.01). Inflammatory lesions (reddish foci) were identified in the liver in both groups. These findings demonstrate that LL supplementation affected specific protozoal population, fibrolytic activity, and gastrointestinal morphology. Further study on a larger number of animals is recommended to validate the effects and assess the safety and efficacy of LLs as a dietary additive in ruminant nutrition.